Development of monoclonal antibody-based enzyme-linked immunosorbent assay for quantitative quality control of Derris scandens (Roxb.) Benth. Issue 4 (4th July 2019) - Jutathis, Kamonthip; Pongkitwitoon, Benyakan; Sritularak, Boonchoo; Tanaka, Hiroyuki; Putalun, Waraporn
ABSTRACT: Derris scandens (Roxb.) Benth. is a medicinal plant used for treatment of musculoskeletal pain in Thai traditional medicines. Its stem contains active compound genistein-7-O-[α-rhamnopyranosyl-(1 to 6)-β-glucopyranoside] (GTG) which is used as a biomarker for standardization of D. scandens extracts. As an alternative for rapid quantitation of GTG, a monoclonal antibody against GTG was prepared and applied for an indirect competitive enzyme-linked immunosorbent assay (ELISA) to determine GTG in plants and herbal products. The established method provided a quantification range of 0.31–10 µg/mL with a limit of detection of 0.29 µg/mL. The assay was validated for precision and accuracy by intra- and interassay variation analyses, recovery test, and comparison analysis between the amounts of GTG determined by ELISA and HPLC. The results exhibited that the developed ELISA is sensitive and effective for determination of GTG in D. scandens plant materials and herbal products.